DETERMINANTS OF FACTORS THAT AFFECT THE STOCK PRICES OF MANUFACTURING COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE IN THE YEARS 2011 - 2015 - Athman, Wahida Jamal (2016)
The Capital Market is a means in which treasury securities are long-term traded. In Capital Markets, companies get funds relatively expensive, because the company does not have to pay the capital cost or the capital cost can be reduced. Securities traded in the in Capital Markets are shares which is the proof of ownership or possession of the shares. There are various factors that affect the price of shares. There are internal as well as external factors. The purpose of this research is to determine to what extent the internal factors Price Earning Ratio, Debt to Equity Ratio, Return on Assets, Price to BookValue ration affects the Stock Price of manufacturing companies that are listed in the Indonesia Stock Exchange during the period of 2011- 2015. A total of 487 companies are listed in the IDX. The data used is secondary data. The analysis technique used is multiple linear regression with a series of test. The results showed that PER, ROA, PBV and EPS have positive effect on the Stock Price; wheres only the EPS showed that it has a negative influence on the Stock Price. Altogether, all the variables used in this research showed that they have a significant influence to the Stock Price to the extent of 13.20 % only.